Violated: sexual consent and assault in the twenty-first century - Fennell, Julie (Rowman & Littlefield, 2024)
"Sexual consent as straightforward, easy, and simple to obtain has become a hallmark of social activism and socially conscious conversation around rape and sexual assault; however, sexual consent often isn't straightforward and simple. Otherwise, we wouldn't need to be having so many long and complicated conversations about it. There are flagrant sexual consent violations that happen all the time, but society and the law are most likely to ignore them. Violated: Sexual Consent and Assault in the 21st Century zeroes in on three main issues that desperately need correcting in our cultural conversations about consent. The first of these is the vision that society and the law have about the meaning of sexual "consent" for men and women, such that women's bodies are regarded as sexually fragile and their sexual consent as precious, while men's bodies are regarded as sexually utilitarian and their consent as irrelevant. The second is our social and legal failure to recognize that some types of sexual assault are worse than others, or to understand that the intentions of the violator matter. Third is the problematic way that activists have ended up eschewing the law and the criminal justice system and use a social version of "self-help" to reform; yet there are many specific legal reforms pertaining to consent and sexual assault that are desirable and necessary for social, cultural, and ethical reasons. Broken into two parts, Violated explains and identifies the social problems that underlie issues of consent and sexual violation, and how they have emerged over time; it then proposes specific social, cultural, and legal reforms to help reduce consent violation. These proposed changes include everything from improving formal sexual education to banning single-sex fraternity houses to clarifying the legal perspective about the mens rea (mental states) required of perpetrators (and survivors) in cases of sexual assault"--